2011
DOI: 10.1103/physrevb.83.174414
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy magnetic excitations in Co/CoO core/shell nanoparticles

Abstract: We have used inelastic neutron scattering measurements to study the magnetic excitations of Co core/CoO shell nanoparticles for energies from 0-50 meV. Above the blocking temperature TB, broad quasielastic scattering is observed, corresponding to the reorientation of the Co core moments and to paramagnetic CoO scattering. Below TB, two nearly dispersionless inelastic peaks are found, whose energies increase with decreasing temperature as order parameters, controlled by the nanoparticle Néel temperature TN =235… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 84 publications
2
22
0
Order By: Relevance
“…We therefore have no evidence for the low-energy spin excitations claimed to be seen in Ref. 40 below the gapped (∼25 meV) onemagnon excitations described previously.…”
Section: Search For Low-energy Crystal Fieldsmentioning
confidence: 52%
“…We therefore have no evidence for the low-energy spin excitations claimed to be seen in Ref. 40 below the gapped (∼25 meV) onemagnon excitations described previously.…”
Section: Search For Low-energy Crystal Fieldsmentioning
confidence: 52%
“…A key difference between MnF 2 and both α-CoV 3 O 8 and FeF 2 is the presence of strong crystal field effects and spin-orbit coupling in the latter two compounds 133,175 . It is also worth noting that unlike the case of pure CoO 81,91,94,[181][182][183][184] where the large and far reaching exchange constants result in a significant and ultimately problematic entanglement of spin-orbit levels 94 , in the case of α-CoV 3 O 8 , the exchange constants are weak and the Weiss temperature is near 0 K. Both observations suggest that the presence of both strong crystal field effects and spin-orbit coupling with well-separated j eff manifolds, as is the case for α-CoV 3 O 8 , may be central to making the dynamics robust against strong disorder.…”
Section: Comparison Between α-Cov3o8 and Randommentioning
confidence: 99%
“…It is found that above some threshold magnetic field the uniform precessional mode, i.e., the k = 0 magnons decay into nonuniform magnons (k = 0), i.e., the Zeeman energy stays in the magnetic subsystem and scatters between magnon modes. [17][18][19][20] However, in ultrafast magnetization reversal the high-energy electrons generated by the laser field decay into the lower-energy magnon excitations. [22][23][24] In both cases spin-orbit coupling (SOC) is responsible for the transfer of the angular momentum to the lattice through different scattering mechanisms such as magnon-magnon, magnon-phonon, magnon-impurity scattering, and so on, where each process has a different relaxation time.…”
mentioning
confidence: 99%
“…12 In current devices the switching speeds have reached a point where dynamical effects are becoming very important [12][13][14][15][16] Magnons are created in fast (field driven) as well as ultrafast (laser induced) magnetization reversal processes. [17][18][19][20][21][22][23][24][25][26] The former case is of particular interest for current device applications. It is found that above some threshold magnetic field the uniform precessional mode, i.e., the k = 0 magnons decay into nonuniform magnons (k = 0), i.e., the Zeeman energy stays in the magnetic subsystem and scatters between magnon modes.…”
mentioning
confidence: 99%